Evaluation of solvent extraction of Amaranth betacyanins using multivariate analysis - Chong, P. H.; Yusof, Yus Aniza; Aziz, Mohammad Gulzarul; Naim, Mohd Nazli; Chin, Nyuk Ling; Syed Muhammad, Sharifah Kharidah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The present study was aimed at assessing the effect of solvents on the yield and the color properties of amaranth extract. Two species of amaranth namely Amaranthus gangeticus and Amaranthus blitum were extracted with water, methanol and ethanol. Seven parameters like betacyanin content, total soluble solids, lightness (L* ), redness (a* ), yellowness (b* ), hue angle (h* ) and chroma (c* ) were analyzed to assess extraction efficiency. Correlation analysis was carried out to assess the linear association among the analytical variables. Principal component analysis was used to establish the relationships between the different analytical variables and to detect the most important factors of variability. Among the two varieties, Amaranthus gangeticus extract contained about two and half time more betacyanin with half of total soluble solids compared to Amaranthus blitum. Water is the best as solvent for extracting betacyanin from Amaranthus gangeticus and ethanol in case of Amaranthus blitum. Among the analytical parameters, a* and c* were perfectly correlated. Three principal components were found among the seven analytical variables accounting 88% of total variability. The first principal components mostly reflected the redness (a* ), whereas the second principal components reflected the betacyanin content, total soluble solids and lightness (L* value).